Pengaruh Promosi Akun Instagram @Rempahbakar.Id Terhadap Minat Beli Followers - Annisa Sri Husniati (Faculty of Social, Politic, and Law Science, Universitas Serang Raya, 2023)
This research examines the use of digital technology, namely Instagram, as a means of promoting culinary spices. Through Instagram, the culinary entrepreneur is targeting the current generation who have physical characteristics, namely making the virtual world a part of their reality. Questionnaires were distributed to a number of followers of the Instagram account @umbubakar.id with a population calculation of 100 followers from 23,300 followers per March. Data were analyzed using descriptive statistics and simple linear regression. This study concludes that Instagram has a significant effect on the purchase intention of followers. However, more interesting and interactive content strategies and promotions are needed.